Optimization of welding strength in the tungsten inert gas welding process for aluminium alloys - Gupta, Amit; Ranjan, Rajeev; Cep, Robert; Kumar, Ajay; Jha, Sanjay Kumar; Altarazi, Faisal; Kumar, Ashish; Dogra, Namrata (Frontiers in Mechanical Engineering, 2025)
Aluminium alloys, particularly AA 6065 T6, are widely used in automotive components such as coolers and radiators due to their excellent strength-to-weight ratio and corrosion resistance. However, welding these alloys presents significant challenges, as the weld joints are prone to thermal stresses, leading to defects and eventual failure. To address this issue, optimizing the PCTIG (Pulsed Current Tungsten Inert Gas) welding process parameters is crucial for achieving superior mechanical properties, particularly tensile strength. This study investigates the influence of peak current, base current, and frequency on the tensile strength of AA 6065 T6 aluminium alloy with varying thicknesses (3 mm, 6 mm, and 10 mm). Regression models are developed to predict tensile strength across the factorial space, and ANOVA is applied to assess the significance of each parameter. Experimental results identify optimal tensile strengths of 179.50 MPa, 188.92 MPa, and 201.22 MPa for 3 mm, 6 mm, and 10 mm thick materials, respectively, with process parameters set at 180 A peak current, 60 A base current, and 2 Hz frequency. Validation through simulation software corroborates these findings, confirming the effectiveness of the optimized parameters in producing defect-free, high-strength weld joints suitable for automotive applications.